Analysis of turbidity current plunging and floating woody debris in a reservoir during flood events - Fong-Zuo Lee; Jihn-Sung Lai; Sameh Ahmed Kantoush; Tetsuya Sumi (Journal of Hydrology: Regional Studies)
Study region: Many reservoirs worldwide experience the challenge of managing woody debris and determining the feasible location to set a floating barrier as a mitigation strategy to restrict their progression towards the dam. While the turbidity current plunges along the reservoir bed to form the underflow mud layer, the reverse current generated in the plunging flow region holds the woody debris. Study focus: The present study attempts to define the plunging zone in correlation with the floating woody debris based on field observations, densimetric Froude number, plunging formula, and entrainment formula to investigate the plunge point location. When woody debris is carried by the sediment-laden inflow through the reservoir, the volume of woody debris needs to be estimated and extracted after the flood recession. New hydrological insight for the region: According to the results of the analysis, the plunge point location was suggested as the critical condition of the densimetric Froude number for a floating barrier setup. Two proposed equations are presented to identify the turbidity current vertical profiles of velocity and sediment concentration. Considering hydrological conditions, the inflow peak sediment yield has added an optimal quantitative estimation of woody debris volumes than that by inflow peak discharge, total inflow sediment yield, maximum rainfall intensity, and total rainfall. The presented threshold values of hydrological patterns can serve as a critical warning indicator for the preparation of extraction operations for floating woody debris.